The Crisis of Multiculturalism in Modern Germany - Zufarovich Galiullin, Marat (2021)
Мigration is one of the main factors, which is creating the modern world, with more than 60 million displaced people. The twenty-first century is a migrant century, since global mobility is a highly stratified phenomenon, ranging from a simple tourist to an illegal worker; Or as a "product" of traffickers to refugee status forced to leave their origin country because of climate change, poverty or wars. Thus, (forced) migration contributes to changes in the structures and institutions of global political, economic and social relations. Nowadays two major demographic trends in the European Union are: continuous population ageing and increasing of migration flows. The abolition of internal borders within the EU has contributed to the spread of concerns caused by security shortages and new challenges, leading to strengthen politicization and securitization of migration and granting shelter. There have been recent discussions in Germany about immigration, integration and multiculturalism. German Chancellor Angela Merkel acknowledged the crisis of Germany 's multiculturalism system. She also said efforts by the US and UK to promote diversity had only led to a weakening of national identity and increased extremist voices in immigrant communities. It is believed, that multiculturalism seems to have come its way. The multiculturalism has been criticized by the European Union. Criticism of far-right diversity management strategy has become a major part of European politics. In addition, from Scandinavian countries to Greece, anti-immigration parties and the number of votes has increased among the population concerned about the effects of growing diversity.